Characterization of tropical starches modified with potassium permanganate and lactic acid - Takizawa,Fabiano Franco (2004)
In the present work some tropical starches were modified by an oxidative chemical treatment with potassium permanganate and lactic acid. The native and modified samples were evaluated by mid-infrared spectroscopy, differential dyeing, pH, expansion power, solubility and swelling power, clarity of the pastes, susceptibility to syneresis, carboxyl content and reducing power. All modified samples presented dark blue color, higher expansion power (except corn starch), carboxyl content and reducing power. The solubility of the modified starch granules was very high at 90ºC. At this temperature, it was not possible to measure their swelling power. The viscographic analysis showed decrease in peak viscosity and higher degree of cooking instability. The principal component analysis of the mid-infrared spectra allowed separation between native and modified samples due to the presence of carboxyl groups. The expansion was inversely related with amylose content of the starches.